Gaya Hidup Kafetaria dan Prediktor Preventif Diabetes Mellitus Remaja - Hayati, Mawar; Yusrawati, Yusrawati; Dewi, Fitriana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between cafeteria lifestyle and preventive predictors of diabetes mellitus in adolescents in the city of Lhokseumawe. This type of research is quantitative with a cross-sectional survey method approach. The research results show a relationship between the cafeteria lifestyle and preventive predictors of diabetes mellitus in adolescents (p-value 0.05). In conclusion, a cafeteria lifestyle can increase the risk of diabetes mellitus in adolescents. Keywords: Diabetes Mellitus, Lifestyle, Cafeteria, Teenagers